2013
DOI: 10.1002/jsfa.6388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary transgenic poplar leaf pellets on performance and tissues in rabbits

Abstract: We conclude that the processed poplar leaves with foreign chitinase-BmkIT genes had no obviously harmful effects on rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been reported that United State livestock industry annually produced more than nine billions of livestock and over 95% of these animals are raised on GM based diets (Van Eenennaam & Young, ). Various studies have independently demonstrated the nutritional value and safe use of GM crops as a feed ingredients in livestock production (Cheng et al, ; García‐Villalba et al, ; Herman & Price, ; Hollingworth et al, ), and insignificant changes related to health, performance and feed digestibility were recorded (Flachowsky, Schafft, & Meyer, ; Mao et al, ; Rahman, Zaman, Shaheen, Irem, & Zafar, ; Salisu, Shahid, Ali, Rao, & Husnain, ; Shahid et al, ; Yang, Sun, Hao, & Wang, ; Yang, Sun, Wang, & Hao, ; Yuan, Tang, Zhao, Shi, & Wang, ). Studies have also not yet reported significant variations relating to any alterations in the nutrients components of animal products obtained from livestock consuming GM‐based feed (Van Eenennaam & Young, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that United State livestock industry annually produced more than nine billions of livestock and over 95% of these animals are raised on GM based diets (Van Eenennaam & Young, ). Various studies have independently demonstrated the nutritional value and safe use of GM crops as a feed ingredients in livestock production (Cheng et al, ; García‐Villalba et al, ; Herman & Price, ; Hollingworth et al, ), and insignificant changes related to health, performance and feed digestibility were recorded (Flachowsky, Schafft, & Meyer, ; Mao et al, ; Rahman, Zaman, Shaheen, Irem, & Zafar, ; Salisu, Shahid, Ali, Rao, & Husnain, ; Shahid et al, ; Yang, Sun, Hao, & Wang, ; Yang, Sun, Wang, & Hao, ; Yuan, Tang, Zhao, Shi, & Wang, ). Studies have also not yet reported significant variations relating to any alterations in the nutrients components of animal products obtained from livestock consuming GM‐based feed (Van Eenennaam & Young, ).…”
Section: Introductionmentioning
confidence: 99%